Helicobacter pylori infection: prevalence, demographic characteristics, clarithromycin resistance and evaluation of the in-house rapid urease test in Sungai Buloh Hospital, Malaysia - Nor Akmal Mokhtar,; Najihan Abdul Samat Muttaqillah,; Salaswati Hussin,; Tuan Suhaila Tuan Soh,; Zubaidah Abdul Wahab,; Mohammad Shukri Jahit, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Helicobacter pylori infection remains an essential global research focus, and increasing clarithromycin resistance was reported to impact the efficacy of clarithromycin-based treatment regiments. The study objectives sought to understand the prevalence of H. pylori infection amongst patients from Sungai Buloh Hospital, Malaysia, its association with demographic factors, and the clarithromycin resistance rate. The in-house rapid urease test (IRUT) was also evaluated and compared to the Campylobacter-like organism (CLO) test using culture or histopathological testing as the gold standard for diagnosis. The gastric corpus biopsies of 352 patients were included, as well as their age group, gender and ethnicity. Clarithromycin susceptibility was measured using the E-test method. The overall prevalence of H. pylori infection was 15.1% (53/352). There was no significant association between the age groups, gender and ethnicity with regards to H. pylori infection. Four of the 13 viable isolates (30.8%) were clarithromycin-resistant. Although IRUT had a slightly lower specificity (94.9%) than that of the CLO test (95.9%), both tests had the same sensitivity values (81.1%). IRUT had a lower positive predictive value (74.1%) than the CLO test (78.2%) but showed a similar negative predictive value (96.5%) compared to the CLO test (96.6%). Both tests displayed a very good agreement (κ = 0.97). In conclusion, the overall prevalence of H. pylori infection in our study was generally low. The high proportion of clarithromycin-resistant isolates may not reflect the exact resistance rate due to the small number of positive cultures. Our IRUT is an acceptable alternative to the CLO test for the rapid diagnosis of H. pylori infections based on its comparable performance.